Association between postpartum depression and the practice of exclusive breastfeeding in the first three months of life - Catarine S. Silva; Marilia C. Lima; Leopoldina A.S. Sequeira-; Juliana S. Oliveira; Jailma S. Monteiro; Niedja M.S. Lima; Rijane M.A.B. Santos; Pedro I.C. Lira (Elsevier, 2017)
Objective: To investigate the association between postpartum depression and the occurrence of exclusive breastfeeding. Method: This is a cross-sectional study conducted in the states of the Northeast region, during the vaccination campaign in 2010. The sample consisted of 2583 mother-child pairs, with children aged from 15 days to 3 months. The Edinburgh Postnatal Depression Scale was used to screen for postpartum depression. The outcome was lack of exclusive breastfeeding, defined as the occurrence of this practice in the 24 h preceding the interview. Postpartum depression was the explanatory variable of interest and the covariates were: socioeconomic and demographic conditions; maternal health care; prenatal, delivery, and postnatal care; and the child's biological factors. Multivariate logistic regression analysis was conducted to control for possible confounding factors. Results: Exclusive breastfeeding was observed in 50.8% of the infants and 11.8% of women had symptoms of postpartum depression. In the multivariate logistic regression analysis, a higher chance of exclusive breastfeeding absence was found among mothers with symptoms of postpartum depression (OR = 1.67; p < 0.001), among younger subjects (OR = 1.89; p < 0.001), those who reported receiving benefits from the Bolsa Família Program (OR = 1.25; p = 0.016), and those started antenatal care later during pregnancy (OR = 2.14; p = 0.032). Conclusions: Postpartum depression contributed to reducing the practice of exclusive breastfeeding. Therefore, this disorder should be included in the prenatal and early postpartum support guidelines for breastfeeding, especially in low socioeconomic status women. Resumo: Objetivo: Verificar a associação entre a depressão pós-parto e a ocorrência do aleitamento materno exclusivo. Método: Estudo de corte transversal realizado nos estados da região Nordeste, durante a campanha de vacinação de 2010. A amostra consistiu de 2583 binômios mães-crianças com idade entre 15 dias e 3 meses. Utilizou-se a Escala de Depressão Pós-Parto de Edimburgo para rastrear a depressão pós-parto. O desfecho consistiu da ausência de aleitamento materno exclusivo nas 24 horas que antecederam a entrevista. A depressão pós-parto foi variável explanatória de interesse e as covariáveis foram: as condições socioeconômicas e demográficas, assistência pré-natal, ao parto e pós-natal, e fatores da criança. Realizou-se análise de regressão logística multivariada com o objetivo de controlar possíveis fatores de confusão. Resultados: A amamentação exclusiva foi observada em 50,8% das crianças e 11,8% das mulheres apresentaram sintomatologia indicativa de depressão pós-parto. Na análise de regressão logística multivariada foi verificada uma maior chance de ausência do aleitamento materno exclusivo entre as mães com sintomas de depressão pós-parto (OR = 1,67; p < 0,001). Conclusões: A depressão pós-parto contribuiu para redução da prática do aleitamento materno exclusivo. Assim sendo, esse transtorno deveria ser incluído nas orientações de suporte desde o pré-natal e nos primeiros meses pós-parto, especialmente, em mulheres de baixo nível socioeconômico. Keywords: Breastfeeding, Postpartum depression, Weaning, Infants, Child care, Antenatal care, Palavras-chave: Aleitamento materno, Depressão pós-parto, Desmame precoce, Lactentes, Cuidado da criança, Assistência pré-natal